Implementasi Project Based Learning Berbasis Pengembangan Game "Bit and Seeds" untuk Konkretisasi Konsep Abstrak Pemrograman Berbasis Objek - Rifaldi, Muhamad Gaza; Nurhidayatulloh S.Pd. M.T (Educational Technology Journal, 2026)
Object-Oriented Programming (OOP) courses are often perceived as difficult by students due to the highlevel of abstraction. This study aims to implement the Project Based Learning (PjBL) method through thedevelopment of a farming simulation game "Bit and Seeds" to concretely visualize OOP concepts. Theresearch method used is Research and Development (R&D) with a simplified software development model,followed by product evaluation through a project showcase. The research subjects involved 46 respondentsconsisting of students and the general public. Data collection was carried out using a digital questionnairecovering ratings and textual feedback. The results showed that the game product successfully implementedClass, Object, and Inheritance concepts effectively. User acceptance was very high, indicated by anaverage satisfaction score of 9.43 (Very Good Category). User feedback highlighted the strengths of thevisual aspects and provided constructive input for feature additions. This study concludes that game-basedPjBL effectively bridges the understanding of OOP theory and produces a viable output product.